Uneven running: How does trunk-leaning affect the lower-limb joint mechanics and energetics? - AminiAghdam, S.; Karamanidis, K.; Rode, C. (European Journal of Sport Science, 2022)
This study aimed to investigate the role of trunk posture in running locomotion. Twelve recreational runners ran in the laboratory across even and uneven ground surface (expected 10 cm drop-step) with three trunk-lean angles from the vertical (self-selected, ~15°; anterior, ~25°; posterior, ~0°) while 3D kinematic and kinetic data were collected using a 3D motion-capture-system and two embedded force-plates. Two-way repeated measures ANOVAs (a = 0.05) compared lower-limb joint mechanics (angles, moments, energy absorption and generation) and ground-reaction-force parameters (braking and propulsive impulse) between Step (level and drop) and Posture conditions. The Step-by-Posture interaction revealed decreased hip energy generation, and greater peak knee extension moment in the drop-step during running with posterior versus anterior trunk-lean. Furthermore, energy absorption across hip and ankle nearly doubled in the drop-step across all running conditions. The Step main effect revealed that the knee and ankle energy absorption, ankle energy generation, ground-reaction-force, and braking impulse significantly increased in the drop-step. The Posture main effect revealed that, compared with a self-selected trunk-lean, the knee's energy absorption/generation, ankle's energy generation and the braking impulse were either retained or attenuated when leaning the trunk anteriorly. The opposite effects occurred with a posterior trunk-lean. In conclusion, while the pronounced mechanical ankle stress in drop-steps is marginally affected by posture, changing the trunk-lean reorganizes the load distribution across the knee and hip joints. Leaning the trunk anteriorly in running shifts loading from the knee to the hip not only in level running but also when coping with ground-level changes.